The Influence of Psychological Factors on Ethical Decision Making in Islamic Educational Institutions at Assalaam Plus High School - Ahsyaf Muzakki; Mulyawan Safwandy Nugraha (al-Afkar, Journal For Islamic Studies, 2025)
This article was written to examine the influence of psychological factors on ethical decision-making in Islamic educational institutions. The research method used in writing this article is a qualitative method with a descriptive approach. Data collection techniques were carried out through: first, in-depth interviews; second, participant observation and third, documentation. Meanwhile, the data collected through the three techniques above were then checked for validity by checking credibility. Research results The influence of psychological factors on ethical decision-making at SMA Plus Assalaam The module project "The Influence of Psychological Factors in Ethical Decision-Making" provides an important contribution to understanding problems in institutions. By increasing awareness of psychological factors and biases, building emotional management skills, and encouraging collaboration, this module helps educational institutions make more ethical, rational, and sustainable decisions. It also plays a role in creating a healthier organizational culture and improving the quality of well-being of all members of the institution.